2017
DOI: 10.1007/s12035-017-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Molecular Genetic Study of 50 Families with Autosomal Recessive Parkinsonism Revealed Known and Novel Gene Mutations

Abstract: In this study, the role of known Parkinson's disease (PD) genes was examined in families with autosomal recessive (AR) parkinsonism to assist with the differential diagnosis of PD. Some families without mutations in known genes were also subject to whole genome sequencing with the objective to identify novel parkinsonism-related genes. Families were selected from 4000 clinical files of patients with PD or parkinsonism. AR inheritance pattern, consanguinity, and a minimum of two affected individuals per family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 43 publications
1
80
0
1
Order By: Relevance
“…Mouse models present with neurodegeneration and enlarged endolysosomal vacuoles, recapitulating the neuropathological findings from human subjects . In the few patients reported on so far, age of onset seems to range from 1.5 to 13 years, with onset of dystonia in a limb with rapid generalization affecting gait . Imaging may demonstrate diffusion restriction in the striatum and susceptibility‐weighed hypointensity in the pallidum and SN (Supporting Information Table S2).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Mouse models present with neurodegeneration and enlarged endolysosomal vacuoles, recapitulating the neuropathological findings from human subjects . In the few patients reported on so far, age of onset seems to range from 1.5 to 13 years, with onset of dystonia in a limb with rapid generalization affecting gait . Imaging may demonstrate diffusion restriction in the striatum and susceptibility‐weighed hypointensity in the pallidum and SN (Supporting Information Table S2).…”
Section: Discussionmentioning
confidence: 71%
“…The duplication was thought to be an incidental finding, given mismatch between patient and typical phenotype. Upon reviewing the areas of homozygosity, the VAC14 gene stood out as a potential candidate based on previous reports …”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…SVs (exon rearrangements) are the most common type of mutations, being identified in about 43.2% of the reported patients (Kasten, et al, ). In a large multicenter study, where we identified PRKN mutations in 71.42% of the examined patients, SVs were the most prevalent mutations identified in the Iranian PD population (Taghavi et al, ). The most common PRKN SV identified to date in the PD population is the c.(171+1_172‐1)_(412+1_413‐1)del mutation, which consists of a deletion encompassing the entire exon 3 of the PRKN gene (https://www.mdsgene.org) (Kasten, et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Another homozygous mutation R459P in SYNJ1 was identified in an Indian family (Kirola, Behari, Shishir, & Thelma, ). Recently, Taghavi et al., () published a SYNJ1 p.R839C mutation in two Iranian siblings with poorly levodopa‐responsive Parkinsonism and generalized seizures since 24 years of age associated with longitudinal tongue fissures. All affected individuals showed early progressive Parkinsonism symptoms in their twenties in combination with cognitive decline or early‐onset refractory seizures (Krebs et al., ; Olgiati et al., ).…”
Section: Introductionmentioning
confidence: 99%